Optimized DNA extraction and library preparation for minute arthropods: Application to target enrichment in chalcid wasps used for biocontrol. (20th April 2019) - Cruaud, Astrid; Nidelet, Sabine; Arnal, Pierre; Weber, Audrey; Fusu, Lucian; Gumovsky, Alex; Huber, John; Polaszek, Andrew; Rasplus, Jean‐Yves
Abstract: Target enrichment is increasingly used for genotyping of plant and animal species or to better understand the evolutionary history of important lineages through the inference of statistically robust phylogenies. Limitations to routine target enrichment are both the complexity of current protocols and low input DNA quantity. Thus, working with tiny organisms such as microarthropods can be challenging. Here, we propose easy to set up optimizations for DNA extraction and library preparation prior to target enrichment. Prepared libraries were used to capture 1, 432 ultraconserved elements (UCEs) from microhymenoptera (Chalcidoidea), which are among the tiniest insects on Earth and the most commercialized worldwide for biological control purposes. Results show no correlation between input DNA quantities (1.8–250 ng, 0.4 ng with an extra whole genome amplification step) and the number of sequenced UCEs on an Illumina MiSeq. Phylogenetic inferences highlight the potential of UCEs to solve relationships within the families of chalcid wasps, which has not been achieved so far. The protocol (library preparation + target enrichment) allows processing 96 specimens in five working days, by a single person, without requiring the use of expensive robotic molecular biology platforms, which could help to generalize the use of target enrichment for minute specimens.